Group work activity to enhance students' courage in delivering questions during online learning: A classroom action research - Retnaningsih, Retnaningsih (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
The objective of this study is to find out the effectiveness of group work strategy in maximizing the students' courage in delivering questions during the online classes. In particular, this study will examine theories on learning, online learning, group work, and courage in delivering questions as part of character building. The approach to be applied in this research is quantitative methods. The research design implemented in this study is classroom action research for 36 students of Class XII IPS 1 at SMAN 9 Semarang. The technique of collecting data uses observation techniques, interviews, and documentation studies. The results show that Learning with the group work can increase the courage of students to ask questions up to more than 75% which shows the effectivity of the strategy and the teacher's strategy in determining the persons involving in a group work plays a significant role in the success of group work and the motivation to deliver questions during the online classes.